20 Investigating sodium-glucose co-transporter 1 (SGLT1) in myocardium and its role in hyperglycemia ischaemia-reperfusion injury. (17th July 2020) - Almalki, Alhanoof; Harding, Idris; Jasem, Hussain; Arjuin, Sapna; Yellon, Derek; Bell, Rob
Abstract : Introduction: Hyperglycaemia is a common finding in diabetic and non-diabetic patients presenting with ACS, and is a powerful predictor of prognosis and mortality. The role of hyperglycaemia in ischemia-reperfusion injury (IRI) is not fully understood, and whether the Sodium Glucose co-Transporter 1 (SGLT1) plays a role in infarct augmentation, before and/or after reperfusion, remains to be elucidated. However, diabetes clinical trials have shown SGLT inhibition improves cardiovascular outcomes, yet the mechanism is not fully understood. Purpose: (1) Characterise the expression of SGLT1 in the myocardium, (2) determine the role of high glucose during IRI, (3) whether SGLT1 is involved in a glucotoxicity injury during IRI, and (4) whether inhibiting SGLT1 with an SGLT inhibitor may reduce infarct size. Methods: RT-PCR and in-situ hybridization (RNAScope) techniques were used to detect SGLT1 mRNA expression in Sprague-Dawley whole myocardium and isolated primary cardiomyocytes. An Ex-vivo Langendorff ischemia-reperfusion perfusion model was used to study the effect of high glucose (22mmol) on the myocardium at reperfusion compared to normoglycaemia (11mmol). The mixed SGLT1&2 inhibitor, Phlorizin was introduced following ischaemia, at reperfusion and its effect on infarct size measured using triphenyltetrazolium chloride (TTC) staining. Results: RT-PCR found SGLT1 mRNA is expressed in whole myocardium and in individual cardiac chambers. SGLT1 expression was not detected in isolated cardiomyocyte but it is detected in the non-cardiomyocyte population. Cardiomyocytes were found to express mRNA SGLT1 if incubated overnight. RNAscope detected SGLT1 mRNA within intact myocardium: not in the cardiomyocyte, but rather in a perivascular distribution. Importantly, hyperglycaemia (22mmol) at reperfusion increased infarct size (51.80 ± 3.52% vs 40.80 ± 2.89%; p-value: 0.026) compared to normoglycaemia, and the mixed SGLT inhibitor, Phlorizin, significantly attenuated infarct size (from 64.7±4.2%to 36.6±5.8%; p-value<0.01) when given at reperfusion. Conclusion: We have shown that SGLT1 is present in the myocardium, but not expressed in cardiomyocytes. The cell type is yet to be determined, but the distribution of SGLT1 is perivascular. Hyperglycaemia appears augment myocardial infarction and inhibition of SGLT1&2 attenuates this increase. We suspect SGLT1 may plays a role in exacerbating the injurious effect of glucotoxicity during ischemia-reperfusion. Conflict of Interest: No